Impacts of Macroeconomic and IPO Factors on Under-pricing of Initial Public Offerings on the National Stock Exchange (NSE) in India - Kedar M Phadke; Dr. Manoj S Kamat, (International Journal of Management Studies (IJMS), 2021)
Underpricing of Initial Public Offerings (IPO) is observed when companies go public as a means to raise capital. This results in significant first day returns for investors which also imply that issuers leave significant money on the table that they could have otherwise raised by correctly pricing their issues. This paper investigates the extent to which local economic as well as IPO specific factors explain first-day marginally adjusted return on opening (MAARO). This study analyzes the MAARO of 239 underpriced IPOs observed for the 2000-2014 period on the NSE. Factors considered for Principal Component Analysis (PCA) wereovernight interbank lending rate, Exchange Rate, Bond Yield, GDP, Interest Rate, M1/M2, Trade Balance, IPI, CPI and average deposit Rate. The results suggest that local economic variables can be summarized by the repo rate and exchange rates. We useMAARO as the dependent variable and the issue type, issue size, subscription rate, repo rate and exchange rate as the independent variables. There is a negative relationship observed between large cap and mid cap stocks to MAARO. There is also a positive relationship observed between subscription rate and repo rate to MAARO. As expected there is a strong negative relation between Bookbuilt IPOs and MAARO. The only exception is the exchange rate where we could not establish any statistically significant relationship between the exchange rate and the level of underpricing in the Indian context for the period 2000 until 2014.